2009
DOI: 10.1002/ana.21615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drugs on lipids, homocysteine, and C‐reactive protein

Abstract: Switching epilepsy patients from the enzyme-inducers carbamazepine or phenytoin to the noninducing drugs levetiracetam or lamotrigine produces rapid and clinically significant amelioration in several serological markers of vascular risk. These findings suggest that phenytoin and carbamazepine may substantially increase the risk for cardiovascular and cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
181
3
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(213 citation statements)
references
References 36 publications
(57 reference statements)
18
181
3
11
Order By: Relevance
“…For example, they alter lipid profile, increasing serum cholesterol levels (Mintzer et al., 2009). However, there is a lack of information about the prevalence of dyslipidemia related to the use of AEDs, which would facilitate appropriate management to reduce the risk of vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they alter lipid profile, increasing serum cholesterol levels (Mintzer et al., 2009). However, there is a lack of information about the prevalence of dyslipidemia related to the use of AEDs, which would facilitate appropriate management to reduce the risk of vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This result goes hand in hand with many studies [30] reported reduction of CRP level in patients treated with VPA, in agreement with Mintzer [31] who also reported that patients who were switched from inducing to non-inducing agents had marked reductions in CRP. This suggests that CYP450 induction may be responsible for CRP level increase [32].…”
Section: Discussionmentioning
confidence: 93%
“…This might be explained by the fact that only a minority of AED users had an epilepsy diagnosis in our cohort and by the difference in methods, where they assessed drug use at 2 time points rather than as a continuous exposure, which makes their results questionable. According to previous studies,23, 24, 25 some AEDs (eg, phenytoin and carbamazepine) seem to induce atherogenic serum cholesterol levels and thus can accelerate atherosclerosis and elevate the risk of cerebrovascular events. However, in our data, the most commonly used AEDs were valproic acid and pregabalin, and they are not known to induce atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…As some AEDs have been linked to accelerated atherosclerosis23, 24, 25 one possibility would have been to assess major adverse cardiovascular events as an outcome. We limited our study to stroke because the aim of this study was to investigate whether AEDs as central nervous system–acting drugs are related to stroke risk in people with AD and because strokes can further accelerate cognitive deterioration in this group.…”
Section: Discussionmentioning
confidence: 99%